Effects of core strength training using stable and unstable surfaces on physical fitness and functional performance in professional female futsal players - Lago-Fuentes, C.; Rey, E.; Padron-Cabo, A.; Sal de Rellán-Guerra, A.; Fragueiro-Rodriguez, A.; Garcia-Núnez, J. (Journal of Human Kinetics, 2018)
The aim of this study was to assess the effect of core strength training performed on a stable surface (CTS) compared with core strength training performed on an unstable surface (CTU) on physical fitness (jump performance, sprint, and repeated sprint ability (RSA)) and quality of movement (Fundamental Movement Screen) in professional female futsal players. Fourteen professional female futsal players (mean age: 23.7 ± 5.1 years, age range: 18-28 years) were randomly assigned to a CTS (n = 7) or a CTU (n = 7) group. The intervention program was carried out 3 times a week over 6 weeks. Players of both groups performed the same four core-strengthening exercises. The only difference between the two interventions was that the CTU group performed all exercises (i.e., shoulder bridge, side bridge, prone plank, and crunch) on an unstable surface (Togu® Dyn-Air). Within-group analysis showed significant improvements (p < 0.001) in 10 m sprint performance from the pre- to post-test in the CTS (+4.37%) and CTU (+5.00%) groups. Players in both the CTS (+10.39%) and CTU (+11.10%) group also showed significant enhancement in the Functional Movement Screen total score, from the pre-test to post-test. In addition, a significant time effect was also observed for the CTU group in the relative score of the RSA test decreasing from the pre- to post-test (-30.85%). In the between-groups analysis, there were no significant differences between the core strength training groups (CTS vs CTU) in any variable. To conclude, sprint and Functional Movement Screen performance improved following CTS and CTU when conducted in combination with regular futsal training. In addition, CTU had limited benefit in RSA compared to CTS.